Strain-rate frequency superposition in large-amplitude oscillatory shear - Kalelkar, Chirag; Lele, Ashish K.; Kamble, Samruddhi (Physical Review E, 2010)
In a recent work, Wyss et al. [Phys. Rev. Lett. 98, 238303 (2007)] have noted a property of ``soft solids'' under oscillatory shear, the so-called strain-rate frequency superposition. We extend this study to the case of soft solids under large-amplitude oscillatory shear (LAOS). We show results from LAOS studies in a mono-disperse hydrogel suspension, an aqueous gel, and a biopolymer suspension and show that constant strain-rate frequency sweep measurements with soft solids can be superimposed onto master curves for higher harmonic moduli with the same shift factors as for the linear viscoelastic moduli. We show that the behavior of higher harmonic moduli at low frequencies in constant strain- rate frequency sweep measurements is similar to that at large strain amplitude in strain- amplitude sweep tests. We show surface plots of the harmonic moduli and the energy dissipation rate per unit volume in LAOS for soft solids and show experimentally that the energy dissipated per unit volume depends on the first harmonic loss modulus alone, in both the linear and the nonlinear viscoelastic regime.

Rheology and microstructural studies of regenerated silk fibroin solutions - Nisal, Anuya; Kalelkar, Chirag; Bellare, Jayesh R.; Lele, Ashish K. (Rheologica Acta, 2013)
Regenerated silk fibroin solutions (RSF) are produced by dissolving degummed silk fibers in water. We have observed that RSF solutions at a concentration less than 15 % by weight exhibit an unusual gel-like response in conventional shear rheology measurements. At higher concentrations, the response is predominantly viscous (or liquid-like). We have probed this counterintuitive behavior of silk fibroin solutions by using microrheology, and interfacial rheometry. Scattering techniques were also used to understand the microstructure of RSF solutions as a function of the concentration. Our studies suggest that the gel-like response of the RSF solution may result from the formation of an interfacial film at the air-solution interface, which dominates the bulk rheological response.
Keywords: Interfacial rheology; Microrheology; Rheology; Silk